Comparison of viability and phagocytic responses of hemocytes withdrawn from the bivalves Mytilus edulis and Dreissena polymorpha, and exposed to human parasitic protozoa. Issue 1 (January 2020) - Le Guernic, Antoine; Geffard, Alain; Le Foll, Frank; Palos Ladeiro, Mélissa
Graphical abstract: Highlights: Interaction of protozoan–hemocyte of blue mussel and zebra mussel were compared. Without protozoan stress, blue mussel's hemocytes had greater viability and phagocytosis. Hemocytes of both mussels did not react similarly to protozoan oocysts. Abstract: Bivalve molluscs are now considered indicator species of aquatic contamination by human parasitic protozoa. Nonetheless, the possible effects of these protozoa on the immune system of their paratenic hosts are poorly documented. The aim of this study was to evaluate the effects of two protozoa on hemocyte viability and phagocytosis from two mussels, the zebra mussel (freshwater habitat) and the blue mussel (seawater habitat). For these purposes, viability and phagocytic markers have been analysed on hemocytes from mussels without biological stress (control hemocytes), and on hemocytes exposed to a biological stress ( Toxoplasma gondii and Cryptosporidium parvum oocysts). We report, for the first known time, the interactions between protozoa and hemocytes of mussels from different aquatic environments. Zebra mussel hemocytes showed a decrease in phagocytosis of fluorescent microbeads after exposure to both protozoa, while blue mussel hemocytes reacted only to T. gondii oocysts. These decreases in the ingestion of microbeads can be caused by competition between beads and oocysts and can be influenced by the size of the oocysts. New characterisations of their immune capacities, including aggregation, remain to be developed to understand the specificities of both mussels.